Ibrutinib Plus R-ICE Induces Remission in Blastoid Variant Mantle Cell Lymphoma with CNS Relapse - Oh, Timothy S.; Burkart, Madelyn; Behdad, Amir; Savas, Hatice; Karmali, Reem (Case Reports in Hematology, 2022)
Mantle cell lymphoma (MCL) is an aggressive, difficult to treat subtype of lymphoma, resulting in relapses and poor outcomes. Novel agents such as Bruton tyrosine kinase (BTK) inhibitors have been studied in the treatment of relapsed/refractory (R/R) MCL. BTK inhibitor ibrutinib, in particular, has demonstrated improvement in survival outcomes of R/R MCL. Despite these advancements, many cases of MCL, including the more aggressive blastoid and pleomorphic variants, will undergo disease progression leading to poor survival outcomes. Blastoid variant MCL is associated with an increased risk of central nervous system (CNS) involvement, causing high mortality rates. In this case report, we discuss a patient with a diagnosis of blastoid MCL with CNS relapse who achieved a complete response (CR) after receiving standard rituximab plus ifosfamide-carboplatin-etoposide (R-ICE) salvage chemotherapy with the addition of ibrutinib. The patient subsequently underwent autologous stem cell transplantation (autoSCT) and maintained CR with ibrutinib maintenance.